This CORRELATION BETWEEN TEACHER LESSON PLAN AND STUDENTS ACHIEVEMENT IN LEARNING ENGLISH (CASE STUDY AT SMAN 1 LANGSA) - Merina Devira (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This research is about “Correlation between Teacher’s Lesson Plan and Student’s Achievement in Learning English at SMA N I Langsa”. The real problem that the writer wants to discuss here is there any correlation between teacher’s lesson plan and student’s achievement. The source of this research were a file of document English lesson plan made by the teachers in learning result of the student in the first year of SMA N I Langsa. For the population of this study, the writer took all students at the first year. The total number of students is 256 students. To collect the data, the writer only took 15% : 2 classes (66 students) as her sample, for instance, by data collecting the writer used some instrument use the simple and appropriate statistical formula, such as mean, standard deviation and correlation (Pearson Product Moment Correlation). The research result shows that the lesson plan which was made by the English according to the score data given by the lesson plan which was made by the English teacher in SMA N I Langsa I was good enough, and student’s effect in learning according to the score data given by the English teacher belonging to medium category such average score 7. This case shows that there is a real correlation between teacher’s lesson plan and the result achievement in learning. Therefore, the hypothesis of this research can be accepted.